Effects of Fish n-3 PUFAs on Intestinal Microbiota and Immune System - Cinzia Parolini (Marine Drugs, 2019)
Studies over several decades have documented the beneficial actions of n-3 polyunsaturated fatty acids (PUFAs), which are plentiful in fish oil, in different disease states. Mechanisms responsible for the efficacy of n-3 PUFAs include: (1) Reduction of triglyceride levels; (2) anti-arrhythmic and antithrombotic effects, and (3) resolution of inflammatory processes. The human microbiota project and subsequent studies using next-generation sequencing technology have highlighted that thousands of different microbial species are present in the human gut, and that there has been a significant variability of taxa in the microbiota composition among people. Several factors (gestational age, mode of delivery, diet, sanitation and antibiotic treatment) influence the bacterial community in the human gastrointestinal tract, and among these diet habits play a crucial role. The disturbances in the gut microbiota composition, i.e., gut dysbiosis, have been associated with diseases ranging from localized gastrointestinal disorders to neurologic, respiratory, metabolic, ocular, and cardiovascular illnesses. Many studies have been published about the effects of probiotics and prebiotics on the gut microbiota/microbioma. On the contrary, PUFAs in the gut microbiota have been less well defined. However, experimental studies suggested that gut microbiota, n-3 PUFAs, and host immune cells work together to ensure the intestinal wall integrity. This review discussed current evidence concerning the links among gut microbiota, n-3 PUFAs intake, and human inflammatory disease.